Effectiveness of Weather Derivatives as a Cross-Hedging Instrument against Climate Change: The Cases of Reservoir Water Allocation Management in Guanajuato, Mexico and Lambayeque, Peru - Miriam Juarez-Torres; Leonardo Sanchez-Aragon (Inter-American Development Bank (IDB), 2012)
Ongoing climate change will increase competition for water. Diversified demand for waterin contrast with the rigid design of water systems, institutions and infrastructurecould hinder the implementation of adaptation policies in water management for Latin American countries. In this context, weather derivatives are proposed as a complementary mechanism for the successful adoption of more efficient water allocations in irrigation districts. Weather derivatives spread risks and incorporate a better understanding of climate system behavior, strengthening irrigation districts ability to deal with water availability and demand. The model uses a dynamic water resource allocation model, historical precipitation and Intergovernmental Panel on Climate Change (IPCC) scenarios to find optimal water allocation strategies for the baseline scenario and in the presence of climate change. This analysis is applied to two irrigation districts in Latin America: one in Mexico and the other in Peru, with their corresponding particularities and results.
Keywords: G13; O13; O54; Q15; Q25; Q54; 330